PENDEKATAN MEDIA GAMBAR DAN PENCAPAIAN HASIL BELAJAR PADA PEMBELAJARAN IPA DI SD - Agus Samsul Bahri (JURNAL BIOSHELL, 2015)
Teaching activity is an activity attempts to create an atmosphere that encourages initiative, motivation and responsibility of the students to always apply the full potential in building ideas through lifelong learning activities. The experiment was conducted in SDN Wonosari 02 with descriptive qualitative and quantitative approaches. The subjects were students in grade 5 with methods of media images. The results showed that the use of media images in science can improve student achievement, both have high achievement motivation and the motivation of low underachievement. Utilization of media images in science  makes learning more effective and efficient, and fun. The use of diverse media that will give students the chance to learn more thoroughly.Keywords : learning outcomes, media images, science